2014
DOI: 10.3136/fstr.20.939
|View full text |Cite
|
Sign up to set email alerts
|

Flavour Analysis of Stirred Yoghurt with Cheddar Cheese Adding into Milk

Abstract: Yoghurt has the strong flavour produced by adding Cheddar cheese into the milk and cold storage process before the fermentation. The flavour analysis of yoghurt was investigated by e-nose, e-tongue and gas chromatography-mass spectrometry (GC-MS). Yoghurt samples with adding Cheddar cheese or whole milk powder showed significant differences in their e-nose flavour profiles, but their e-tongue flavour profiles were roughly similar. Besides, neither e-nose nor e-tongue could accurately distinguish the yoghurt sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Extensive studies have been reported on improving the flavor properties of fermented milk by adding various food ingredients. Li et al (2014) found that Cheddar cheese addition significantly increased the aroma compounds in fermented milk. Ye et al (2012) studied the effect of hawk tea on yogurt and found that hawk tea could significantly increase the content of acetaldehyde, diacetyl, and acetoin.…”
Section: Introductionmentioning
confidence: 96%
“…Extensive studies have been reported on improving the flavor properties of fermented milk by adding various food ingredients. Li et al (2014) found that Cheddar cheese addition significantly increased the aroma compounds in fermented milk. Ye et al (2012) studied the effect of hawk tea on yogurt and found that hawk tea could significantly increase the content of acetaldehyde, diacetyl, and acetoin.…”
Section: Introductionmentioning
confidence: 96%
“…The first one explains the highest amount of variance, followed by the second component that explains the highest residual variance, and so on. [25,28,29] LDA is a probabilistic parametric classification technique which minimizes the variance between categories by data projection from high-dimensional space to lowdimensional space and maximizes the variance within categories. [22,31,32] Compared to PCA, the LDA method can analyze the distribution of points in the same category and the distance between them.…”
Section: Discussionmentioning
confidence: 99%
“…E-tongue analyses have been used to evaluate the acid, sweet, bitter, salty, and astringent tastes in foods and pharmaceuticals. [28] In this study, the classification results of the flavor compounds in milk were analyzed using an e-tongue equipped with five sensors. Figure 2 shows that DI was 99.2%, indicating that the PCA and LDA analyses of the overall classification were satisfactory.…”
Section: Analysis Of E-tongue Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrometer was run in 70 eV electron ionization mode with the iron source temperature set at 200 °C. Mass scan range was 25 to 400 mass: charge ratio (Li et al., 2014). The volatile compounds were identified by comparison with authentic standards (MS library NIST 08), and the profile of their formation and content was followed by their area counts and relative peak area, respectively.…”
Section: Methodsmentioning
confidence: 99%